Augmentative and alternative communication for Aboriginal Australians: Developing core vocabulary for Yolŋu speakers. (2nd October 2022) - Amery, Rebecca; Wunungmurra, Julie Gungungbuy; Raghavendra, Parimala; Bukuḻatjpi, Gurimaŋu; Dikul Baker, Rachel; Gumbula, Farrah; Barker, Ruth; Theodoros, Deborah; Amery, Howard; Massey, Libby; Lowell, Anne
Abstract: Yolŋu, Aboriginal people from Arnhem Land, Australia are at risk of Machado-Joseph disease, with progressive loss of speech. Yolŋu are interested in developing augmentative and alternative communication (AAC) systems in their own languages. This research aimed to develop a culturally responsive process to explore and create a core vocabulary word list for Yolŋu adults living with the disease for inclusion in AAC system prototypes. A list of 243 Yolŋu words and morphemes was created. In this highly collaborative, mixed methods, participatory action research, Balanda (the Yolŋu word for non-Aboriginal people) and Yolŋu researchers conducted cycles of transcription and analysis of a language sample, with oral group discussions to identify which words to include, omit, or add, based on Yolŋu perceptions of the structure and use of their languages. A Yolŋu metaphor, Gulaka-buma ("Harvesting yams"), was identified by Yolŋu researchers to represent and share the research process and findings. Three key themes were identified that summarize the main cultural and linguistic considerations related to changes made to the core vocabulary. Study findings emphasized the role of language as an expression of culture and identity for Indigenous peoples and the importance of considering cultural and linguistic factors in selecting vocabulary for AAC systems.